PENGARUH KURIKULUM DAN METODE SAINTIFIK TERHADAP KARAKTER PANCASILAIS PADA PENDIDIKAN AGAMA KRISTEN - Ester Widiyaningtyas (STTII PURWOKERTO, 2021)
The moral decline of children in Indonesia requires serious attention through character education in Christian Religious Education to restore future generations to become better, faithful, moral and moral generations to be able to coexist peacefully in the midst of diversity in the Unitary State of the Republic of Indonesia. Through dematerialization of the curriculum based on scientific learning methods in Christian Religious Education, it is hoped that it will not only increase the formation of Christian spiritual character but also in the formation of Pancasilaist character for students.This research approach is quantitative. The type of data used is primary data through a survey using a closed questionnaire. The data analysis technique used is SEM with the PLS (Partial Least Square) program. The results of the analysis show that Curriculum Dematerialization has no significant effect on Character Education (t-table of 0.028) and Pancasilaist Character (t-table of 0.263). Then, the scientific learning method variable has a significant effect on character education with a t-table value of 2.521, and Pancasilaist character (t-table: 2.102). The next finding is that character education has no significant effect on the Pancasilaist character (t-table 0.195) and character education does not mediate the influence of the curriculum and method on the Pancasilaist character. The results of this study can be recommended for improving the learning process of Christian Religious Education in curriculum dematerialization and scientific learning methods through character education in the formation of Pancasilaist character for students at MGMP PAK SMP in Surabaya.Keywords: Curriculum, Scientific Method, Pancasilaist Character